Analysis of Tourist Motivation in Cave Tubing Activities in Pindul Cave - Nufail Naisaburi, Muhammad; Khairune Nisa, An Nuur; Bahri, Iswan; Nurmala Fadin, Delfyan Intan (Jurnal Toursci, 2024)
A popular location for special interest tourism, Pindul Cave is situated in Desa Bejiharjo, Kecamatan Karangmojo, Gunungkidul, and offers cave tubing adventures. By gliding down the tunnel on inner tubes and taking in the beautiful karst scenery, tourists can partake in a sport called "cave tubing." Pindul Cave is a unique destination that attracts tourists drawn to it by favorable impressions of its offerings. Since motivation starts the travel process, it is essential to tourism even if travelers frequently need to recognize its importance. Among the several kinds of tourism, depending on motive, are leisure, convention, sports, cultural, leisure, and business travel. Discovering the local way of life, taking in the scenic surroundings, relaxing, exploring new areas, finding peace, and satisfying one's curiosity are all goals of pleasure tourism. Many travelers have different reasons for visiting Pindul Cave, such as its popularity. Travelers who travel independently (FITs) typically go in small groups of five to ten persons, unlike tourists who come in huge groups escorted by travel agencies. In order to get and evaluate data from several sources and provide essential insights into industry trends and visitor motivations, the talk goes into additional detail about the techniques used, including qualitative research. Furthermore, the discourse encompasses the number of tourists visiting Pindul Cave, their reasons for visiting, and the value addition they perceive from their travels. This thorough investigation clarifies the various facets of tourism dynamics in Pindul Cave.